Identification of Vancomycin Resistance in Methicillin-resistant Staphylococcus aureus in two macaque species and decolonization and long-term prevention of recolonization in Cynomolgus Macaques (Macaca fascicularis) - Bochart, Rachele M.; Armantrout, Kimberly; Crank, Hugh; Tonelli, Rachael; Shriver-Munsch, Christine; Swanson, Tonya; Fischer, Miranda; Wu, Helen; Axthelm, Michael; Sacha, Jonah; Smedley, Jeremy V. (Frontiers in Immunology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a S. aureus strain with resistance to beta-lactam antibiotics, making it a global human and veterinary health concern. Specifically, immunosuppressed patients have a remarkably higher risk of clinical MRSA infections with significantly increased rates of prolonged clinical recovery, morbidity, and mortality. The current treatment of choice for MRSA is vancomycin. Importantly, we report the first known vancomycin-resistant S. aureus (VRSA) carriers in a cohort of Mauritian cynomolgus macaques (CM) imported to the Oregon National Primate Research Center (ONPRC), with a MRSA carrier rate of 76.9% (10/13 animals). All MRSA isolates also demonstrated resistance to vancomycin with prevalence of vancomycin-intermediate Staphylococcus aureus (VISA) at 30% (3/10 MRSA-positive CMs) and VRSA at 70% (7/10 MRSA-positive CMs). Additionally, we identified VRSA in a rhesus macaque (RM) housed within the same room as the VRSA-positive CMs and identified a MRSA/VISA carrier rate of 18.8% in RMs (3/16 positive for both MRSA and VISA) in unexposed recently assigned animals directly from the ONPRC RM breeding colony. Considering that the MRSA and VRSA/VISA-positive CMs future study aims included significant immunosuppression, MRSA/VRSA/VISA decolonization treatment and expanded “MRSA-free” practices were employed to maintain this status. We report the first controlled study using in-depth analyses with appropriate diagnostic serial testing to definitively show an MRSA decolonization therapy (90% success rate) and expanded barrier practice techniques to successfully prevent recolonization (100%) of a cohort of CMs MRSA-free (up to 529 days with a total of 4,806 MRSA-free NHP days).